2022
DOI: 10.1111/jam.15609
|View full text |Cite
|
Sign up to set email alerts
|

Ketoprofen, piroxicam and indomethacin-suppressed quorum sensing and virulence factors in Acinetobacter baumannii

Abstract: Aim Quorum sensing (QS) inhibition is a promising strategy to suppress bacterial virulence and control infection caused by Gram‐negative and Gram‐positive bacteria. This study explores the QS inhibiting activity of the non‐steroidal anti‐inflammatory drugs (NSAIDs) in Acinetobacter baumannii. Methods and Results Ketoprofen, piroxicam and indomethacin revealed QS inhibition via elimination of violacein production of the reporter strain Chromobacterium violaceum ATCC 12472 without affecting bacterial growth. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Previous studies basically focused on determining the acute toxicity of KTP at high concentrations ( Marchlewicz et al, 2017 ; Żur et al, 2018 ; Petrie and Camacho-Muñoz, 2021 ; Praveenkumarreddy et al, 2021 ). For instance, KTP was found to inhibit the quorum sensing of gram-negative pathogens such as Acinetobacter baumannii , Chromobacterium violaceum , and Pseudomonas aeruginosa ( Tajani et al, 2021 ; Vargas et al, 2021 ; Elshaer et al, 2022 ). An intriguing work by Neale et al (2019) aimed to determine the effects of different NSAID enantiomers on the bacterium Photobacterium leiognathi using the Bacterial Luminescence Toxicity Screen.…”
Section: Ecotoxic Effects Of Ketoprofenmentioning
confidence: 99%
“…Previous studies basically focused on determining the acute toxicity of KTP at high concentrations ( Marchlewicz et al, 2017 ; Żur et al, 2018 ; Petrie and Camacho-Muñoz, 2021 ; Praveenkumarreddy et al, 2021 ). For instance, KTP was found to inhibit the quorum sensing of gram-negative pathogens such as Acinetobacter baumannii , Chromobacterium violaceum , and Pseudomonas aeruginosa ( Tajani et al, 2021 ; Vargas et al, 2021 ; Elshaer et al, 2022 ). An intriguing work by Neale et al (2019) aimed to determine the effects of different NSAID enantiomers on the bacterium Photobacterium leiognathi using the Bacterial Luminescence Toxicity Screen.…”
Section: Ecotoxic Effects Of Ketoprofenmentioning
confidence: 99%
“…The method was developed in this concentration range, because IC 50 (concentration, which leads to half the maximum inhibitory effect on the action of pro-inflammatory factor) for S-ketoprofen is 26.7 μg/ml [19] and even higher concentrations of racemic ketoprofen are used for in vitro studies. [20][21][22] For example, in the study by Hara-Yamamura et al HepG2 cells gene expression changes started increasing around 127 μg/mL ketoprofen exposure. [22] In the study by Banach et al the same concentration of ketoprofen in combination with UVA radiation reduced melanoma cells vitality.…”
Section: Discussionmentioning
confidence: 99%
“…In this study was developed and validated method enabling determination of ketoprofen in the calibration range of 5–100 μg/mL. The method was developed in this concentration range, because IC 50 (concentration, which leads to half the maximum inhibitory effect on the action of pro‐inflammatory factor) for S‐ketoprofen is 26.7 μg/ml [19] and even higher concentrations of racemic ketoprofen are used for in vitro studies [20–22] . For example, in the study by Hara‐Yamamura et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some drugs that do not belong to the group of antibiotics and antibacterial chemotherapeutics may have direct ( Tyski 2003 ; Kruszewska et al 2012 ; Laudy et al 2017 ; Lagadinou et al 2020 ; Kruszewska et al 2021 ) or indirect antibacterial activities, e.g., affect the activity of membrane efflux pumps ( Nair et al 2004 ; Laudy et al 2018 ) or the quorum sensing systems ( Gajdács and Spengler 2019 ; Elshaer et al 2022 ). These drugs are called non-antibiotics, and we determined whether frequently and sometimes chronically taken non-steroidal anti-inflammatory drugs (NSAIDs) and pain relief drugs could affect bacteria of the family Lactobacillaceae present in the microbiota, as well as those administered in probiotic preparations.…”
mentioning
confidence: 99%
“…Some studies have shown the effects of NSAIDs on the growth and virulence of symbiotic and pathogenic human bacterial strains. Antibacterial activity has been demonstrated for diclofenac, ibuprofen, acetylsalicylic acid ( Laudy et al 2016 ; Zimmermann and Curtis 2017 ; Lagadinou et al 2020 ), flurbiprofen ( Zimmermann and Curtis 2017 ; Lagadinou et al 2020 ), piroxicam, indomethacin, and ketoprofen ( Elshaer et al 2022 ). Moreover, Laudy et al (2016) showed that ibuprofen, diclofenac, acetylsalicylic acid, and mefenamic acid were substrates for efflux pumps in Gram-negative rods.…”
mentioning
confidence: 99%